An Alternative Approach for Analyzing Stability of Conservative Pipes Conveying Fluid - Yousif, Albert E.; Jweeg, Mohsin J.; Ismail, Mahmud R. (Nahrain University College of Engineering Journal, 2014)
In many classes of problems of elastic systems such as gyroscopic and circulatory systems stability investigations are being conducted .The concept of a "stability boundary" arising in connection with multiple loading parameters is used for stability investigation. The concept is extended to analyze stability of conservative pipes conveying fluid since they are regarded as gyroscopic systems.In this approach the pipe system is discretized to a two –degree of freedom by using Galarkin projection. The solution of the Eigen-value problem leads to the characteristic equation describing the parameters -frequency relationship .By plotting the root locus of these characteristic equation the main stability features such as stability, buckling and flutter instability and destabilization has been investigated graphically .The validity of this approach was tested by comparing it with the other published methods The results gave good agreements.The effect of the fluid parameters such as fluid velocity, fluid pressure and pipe-fluid mass ratio on the pipe stability are also investigated. The results showed that the mass ratio has a major effect on stability behaviors since the sequence of stability can be dramatically changed whereas ,the fluid pressure showed slight effect since the stability sequence is not altered , for wide range of the fluid velocities .